Insights into Recent Studies on Biotransformation and Pharmacological Activities of Ginsenoside Rd - Xiaoping Song; Lina Wang; Daidi Fan (Biomolecules, 2022)
It is well known that ginsenosides—major bioactive constituents of Panax ginseng—are attracting more attention due to their beneficial pharmacological activities. Ginsenoside Rd, belonging to protopanaxadiol (PPD)-type ginsenosides, exhibits diverse and powerful pharmacological activities. In recent decades, nearly 300 studies on the pharmacological activities of Rd—as a potential treatment for a variety of diseases—have been published. However, no specific, comprehensive reviews have been documented to date. The present review not only summarizes the in vitro and in vivo studies on the health benefits of Rd, including anti-cancer, anti-diabetic, anti-inflammatory, neuroprotective, cardioprotective, ischemic stroke, immunoregulation, and other pharmacological effects, it also delves into the inclusion of potential molecular mechanisms, providing an overview of future prospects for the use of Rd in the treatment of chronic metabolic diseases and neurodegenerative disorders. Although biotransformation, pharmacokinetics, and clinical studies of Rd have also been reviewed, clinical trial data of Rd are limited; the only data available are for its treatment of acute ischemic stroke. Therefore, clinical evidence of Rd should be considered in future studies.